The Influence of ZrO2 Additions on Al2O3 Evaporation and AlN Crystal Growth by Thermal Nitridation of Al2O3–ZrO2 Pellets. Issue 10 (27th August 2013) - You, Yu; Kato, Mikako; Ohtsuka, Makoto; Fukuyama, Hiroyuki; Butt, D.
<x xml:space="preserve">Abstract</x> The effects of ZrO2 additions to Al2O3 were investigated to improve the evaporation rate of Al2O3 for bulk AlN crystal growth. The evaporation rate of Al2O3 increased concomitantly with increasing ZrO2 concentration under a nitrogen gas stream at 2223 K. The ZrO2 was predominantly nitrided. The nitridation of ZrO2 kept the local oxygen partial pressure high at the pellet surface, which suppressed the nitridation of Al2O3. The nitridation of ZrO2 caused the outward diffusion of ZrO2 (Zr4+ and O2−) in the pellet, which was accelerated further by the presence of Al2O3–ZrO2 liquid phase in grain boundaries, leading to the prompt formation of ZrN porous layer on the pellet surface. The suppressed nitridation of Al2O3 and the formation of porous ZrN layer were the reasons for the enhanced evaporation of Al2O3, leading to enhanced bulk AlN growth.